SYNTHESIS OF AROMATIC POLYESTERS BASED ON NORBORNANE-CONTAINING DIOLS (World Science, 2022)
Aromatic polyesthers were synthesized on the base of policiclicbisphenols and dichloroanhydride of aromatic dicarboxylic acid by the method of equilibrium polycondensation in solvent. The obtained polymers are characterized by high heat-and thermal stability, are well soluble in chlorinated hydrocarbons and they form transparent films from solutions which are characterized by good mechanical and dielectric properties.